A review of catalysts used in microwave assisted pyrolysis and gasification. (April 2019) - State, Razvan Nicolae; Volceanov, Adrian; Muley, Pranjali; Boldor, Dorin
Highlights: In situ microwave catalytic process is frequently used due to simpler set-up. Ex situ microwave processes can lead to optimum temperatures and better results. Ex situ process has low deactivation rates in situ catalysts deactivate easily. Catalytic microwave-assisted process is favorable for yields and product quality. Commonly used catalysts: zeolites, metal oxides, various salts and carbon materials. Abstract: The review describes different catalysts and reactor-types used in microwave-assisted thermochemical biomass conversion. We present comparative review of various catalytic experiments and experimental conditions using catalysts in both in situ and ex situ processes. In situ catalytic processes are more frequently used due to simpler experimental set up. However, the process leads to higher catalytic deactivation rate and catalyst recovery is difficult. Catalysts used in ex situ processes require a more complex experimental set-up, the advantage being the fact that optimum temperature can be obtained to achieve best results catalyst recovery is facile, and its deactivation occurs at a lower rate. The catalysts described herein represent just a small part of the catalyst types/family that can be theoretically used. Commonly used catalysts are zeolites, metal oxides, various salts or carbon type materials but other materials or improvements of those mentioned need to be tested in the future.